Massive Pulmonary Embolism in a Recent Intracranial Hemorrhage: A Case Report of Inhaled Nitric Oxide to Improve Outcomes - Mittal, Abhinav (Cureus, 2020)
Acute massive pulmonary embolism (PE) has a high mortality if left untreated. The mainstay of treatment is systemic thrombolysis which has some absolute contraindications like intracranial hemorrhage (ICH). Inhaled nitric oxide (iNO) is a selective pulmonary vasodilator that decreases pulmonary artery pressure (PAP) and allows the right ventricle of the heart to pump against less resistance. We present a case of iNO use to improve hemodynamics in a patient with a recent ICH. We believe this to be the first such case reported. A 70-year-old female with a history of PE on Eliquis initially presented for weakness and was found to have right-sided ICH. She was discharged with instructions to hold Eliquis given ICH but was readmitted eight days later in florid cardiogenic shock requiring vasopressors and hypoxic respiratory failure refractory to intubation. CT showed bilateral PE with evidence of right heart strain and IV heparin was started. Due to her history of a recent ICH, she had an absolute contraindication prohibiting the use of systemic tissue plasminogen activator (tPA). Interventional radiology (IR) consult determined that the patient was not a candidate for catheter-directed tPA due to the recent ICH, mechanical ventilation, and hemodynamic instability based on pressor requirement. Vascular surgery and extracorporeal membrane oxygenation (ECMO) consults deemed the patient not operable. The patient was then started on iNO with immediate improvement in her blood pressure. Once vitally stable, IR consult performed pulmonary angiogram and completed a thrombectomy. The patient was eventually extubated and she restarted her Eliquis. She continues to do well 16 months after discharge. In patients with massive PE with contraindications to systemic thrombolytics, providers are left with very few therapeutic interventions. A handful of case reports show that iNO improves systemic hemodynamics in postoperative patients with massive PE. This case highlights the potential for iNO to be a potential adjuvant in patients with absolute contraindications to systemic thrombolysis.